The Influence of Parental Education Level on Learning Discipline of PPKn FKIP Students at Riau University - Mendrofa, Syukur Jaya; Gimin, Gimin; Arianto, Jumili (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
This study is motivated by the role of parents' level of education in guiding and directing their children in the learning process, especially in student learning disciplines. This research aims to determine whether there is an influence between the level of parental education on the learning discipline of PPKn FKIP Riau University students. This research uses quantitative research methods carried out in the PPKn FKIP study program at Riau University with data collection methods using questionnaires and statistical data analysis using SPSS Version 20. Based on the findings from data analysis, the hypothesis test has a calculated f value f table, this shows the alternative hypothesis in this study was rejected. The coefficient of determination value in this study was obtained at 0.006, so it can be concluded that the influence of the parental education level variable on the student learning discipline variable was 0.6%, while the other 99.4% (100% - 0.6%) was influenced by other factors. others not examined in this study.